Psychological and functional outcomes following a randomized controlled trial of surf and hike therapy for U.S. service members - Walter, Kristen H.; Otis, Nicholas P.; Miggantz, Erin L.; Ray, Travis N.; Glassman, Lisa H.; Beltran, Jessica L.; Kobayashi Elliott, Kim T.; Michalewicz-Kragh, Betty (Frontiers in Psychology, 2023)
Introduction Exercise-based interventions have established benefits for the treatment of depression and other psychological outcomes; however, limited data exist evaluating psychological, social, and functional outcomes for exercise outdoors. Methods The current study sought to expand knowledge about the breadth of effects following outdoor exercise interventions by using data from a randomized control trial comparing Surf and Hike Therapy among 96 U.S. active duty service members with major depressive disorder (MDD). Assessments examining psychological symptoms and functioning were completed before and after the 6-week programs, and 3 months following program completion. Participants also completed assessments before and after each exercise session. Multilevel modeling was used to determine whether psychological and functional outcomes (anxiety, positive and negative affect, resilience, pain, and physical and social functioning) improved for service members receiving Surf or Hike Therapy, and whether improvements differed by intervention. Results Study findings showed improved anxiety (p < 0.001), negative affect (p < 0.001), psychological resilience (p = 0.013), and social functioning (p < 0.001) following program participation, with no differences by intervention. Positive affect, pain, and physical functioning did not significantly improve after the program. Within sessions, positive affect (p < 0.001) and pain (p = 0.036) changed, and to a greater extent for those in the Surf Therapy condition. Conclusion Study results suggest that both Surf Therapy and Hike Therapy can improve psychological symptoms and social functioning impairments that commonly co-occur among service members with MDD, but Surf Therapy may provide enhanced immediate effects on positive affect and pain. Clinical trial registration ClinicalTrials.gov, NCT03302611.